City with Smart Waste Management: Introducing Waste Bin Technologies (Nexo Revista Científica, 2021)
Population growth and urbanization have led to an increase in the rate of waste production, the lack of timely and proper management of which will have adverse effects on human life and the environment. Since most of the waste management costs are spent on waste collection and transportation, it is necessary to find solutions to control the huge costs of this sector. On the other hand, today, intelligent technologies are used globally as solutions to meet challenges in various fields such as agriculture to improve agro-industrial production, transportation, and waste management, which creates a concept called smart cities. One of the categories that has changed the concept of cities and made them have easier and smarter answers to various events and needs is the "Internet of Things", in which many cases and infrastructures with new hardware technologies and Software are integrated. Waste collection is no exception to this rule and efforts have been made to make it smarter. In this research, some of the latest innovations presented globally in order to make trash smarter have been examined.